2020
DOI: 10.3389/fonc.2020.601661
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TIM-3 in Hepatocellular Carcinoma: A Promising Target for Immunotherapy?

Abstract: One of the most common tumors in the world is hepatocellular carcinoma (HCC), and its mortality rates are still on the rise, so addressing it is considered an important challenge for universal health. Despite the various treatments that have been developed over the past decades, the prognosis for advanced liver cancer is still poor. Recently, tumor immunotherapy has opened new opportunities for suppression of tumor progression, recurrence, and metastasis. Besides this, investigation into this malignancy due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…In addition to antibodies against CTLA-4 and PD-1/PD-L1, checkpoint inhibitor targeting TIM-3 is another potential and promising candidate of immunotherapy for cancer treatment[ 272 , 299 ]. TIM-3, a type I surface glycoproteins encoded by the gene on chromosome 5q33.2, was first discovered in 2001 and identified as an immune checkpoint that specifically expressed on interferon-γ-secreting CD4(+) T helper 1 and CD8(+) T cytotoxic cells in both mice and humans[ 300 , 301 ]. TIM-3 acts as a negative regulator of T cell function by triggering cell death upon interaction with its ligand, galectin-9.…”
Section: Challenges Of Treating Hcc In Patients With Renal Dysfunctionmentioning
confidence: 99%
“…In addition to antibodies against CTLA-4 and PD-1/PD-L1, checkpoint inhibitor targeting TIM-3 is another potential and promising candidate of immunotherapy for cancer treatment[ 272 , 299 ]. TIM-3, a type I surface glycoproteins encoded by the gene on chromosome 5q33.2, was first discovered in 2001 and identified as an immune checkpoint that specifically expressed on interferon-γ-secreting CD4(+) T helper 1 and CD8(+) T cytotoxic cells in both mice and humans[ 300 , 301 ]. TIM-3 acts as a negative regulator of T cell function by triggering cell death upon interaction with its ligand, galectin-9.…”
Section: Challenges Of Treating Hcc In Patients With Renal Dysfunctionmentioning
confidence: 99%
“…TIM-3 was initially identified as a T cell marker for Th1 and CD8 + T cells. It was later shown that TIM-3 is expressed by human Th1 and Th17 cells and also other immune cells encompassing dendritic cells (DCs), macrophages, and natural killer (NK) cells (Ganjalikhani Hakemi et al, 2020). TIM-3 is expressed on activated T cells, and its signaling on cytotoxic T cells leads to reduction in proliferation, decreased production of effector cytokines and apoptosis of effector T cells.…”
Section: Introductionmentioning
confidence: 99%
“…SREBP-1 (Sterol Regulatory Element Binding Protein-1) and GLUT-1 are important regulators of cellular material and energy metabolism ( 42 45 ) for modulating the microenvironment of tumor cells. Therefore, it is necessary to further examine the participation of the aberrant metabolism of malignant tumor cells in the progress or resistance of cancer cells to antitumor agents ( 46 ).…”
Section: Discussionmentioning
confidence: 99%